Catalyst for synthesizing higher alcohol through CO2 hydrogenation and preparation method and application thereof
The catalyst addresses the inefficiencies of existing CO2 hydrogenation catalysts by using a modified Fe-Zn catalyst with additives, achieving high CO2 conversion and selectivity through mechanical ball milling, suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202411063392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-17
AI Technical Summary
Existing CO2 hydrogenation catalysts face challenges in achieving high CO2 conversion rates and higher alcohol selectivity simultaneously, with traditional methods either having low CO2 conversion rates or high selectivity but inefficient resource utilization.
A catalyst is prepared by introducing specific additives and using mechanical ball milling to improve the dispersion of active components, comprising Fe and Zn with a molar ratio of 2-10:1, along with auxiliary agents like Na, K, Rb, Cs, and Zr, and Mn, and employing a controlled preparation process.
The catalyst achieves high CO2 conversion rates and excellent higher alcohol selectivity, with the best performance at a 3:1 Fe:Zn ratio and Zr as additive II, facilitating scalable and environmentally friendly large-scale production.
Smart Images

Figure BDA0004978659080000081 
Figure BDA0004978659080000101 
Figure BDA0004978659080000121
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation and CO2 resource utilization, and specifically relates to a catalyst for synthesizing higher alcohols by hydrogenating CO2, and a preparation method and application thereof. Background Art
[0002] With the acceleration of industrial development and modern civilization, the extensive use of fossil fuels has led to an increase in the concentration of CO2 in the atmosphere, causing a series of environmental problems and posing a severe challenge to the sustainable development of human society. In order to cope with this problem, CO2 is converted into high-value-added chemicals or fuels, such as higher alcohols (C 2-6 OH, a straight-chain alcohol with 2-6 carbon atoms), has become an important research direction, which is of great significance for reducing greenhouse gas emissions and achieving energy transformation and circular economy. Higher alcohols have attracted much attention due to their high energy density and high octane number, and they are important basic raw materials for energy chemical industry. Traditional methods for producing higher alcohols, such as grain fermentation and olefin hydration, have problems such as long processes and high carbon emissions. In contrast, CO2 hydrogenation to synthesize higher alcohols (CO2-HAS) technology has the potential to replace traditional synthesis methods due to its advantages such as short process and high efficiency.
[0003] In the existing research on CO2-HAS catalysts, the efficient preparation of catalysts is an important bottleneck restricting the development of CO2-HAS technology. 2+ OH selectivity is generally low.
[0004] See “Mn Promoter Effect in CuFe-based Catalysts for CO2 Hydrogenation to Low-carbon Alcohols” published by Zhang Xinxin et al. in the Journal of Chemistry of Universities. It discloses a MnCuFeZn-K catalyst prepared by coprecipitation method and its application in CO2 hydrogenation to C 2+ In the reaction of OH, at 320℃ and 5MPa, the conversion rate of CO2 was 29.4%, and the conversion rate of C 2+ The OH selectivity reached 23.2%. The CO2 conversion rate of the catalyst was 2+ Although the OH selectivity has been improved compared with the past, the CO2 conversion rate and C 2+ There is still much room for improvement in OH selectivity.
[0005] Chinese patent CN116099540A discloses a low-carbon alcohol catalyst of triple sites of indium oxide, transition metal and alkali metal, wherein the indium precursor is dissolved and a precipitant is added to obtain a precipitate, which is stirred, filtered and washed to obtain an indium oxide precursor, which is then dried and calcined, and the indium oxide obtained after calcination is added to an alkali metal auxiliary agent (Na or K) and a metal auxiliary agent (Fe, Co, Ni, Cu, Zn, Mg) precursor solution and stirred, and the obtained complex is dried and calcined, and the catalyst product is obtained after activation in a mixed atmosphere of hydrogen and argon or a carbon monoxide atmosphere. The catalyst C 1-4 The OH selectivity is as high as 95.5%, but the CO2 conversion rate is only 11%-20%. 1-4 The OH selectivity is high but the CO2 conversion rate is low, and the resource utilization efficiency is too low, so there is still a lot of room for improvement.
[0006] In order to solve the problem that the CO2 conversion rate and higher alcohol selectivity of the catalyst cannot be improved simultaneously, the present invention mainly introduces a variety of additives to modify the catalyst, and at the same time uses a mechanical ball milling method to improve the dispersion of the active components to prepare a catalyst with high CO2 conversion rate and good higher alcohol selectivity. This innovative catalyst preparation technology provides new possibilities for the resource utilization of CO2 and the green synthesis of higher alcohols, and has broad application prospects in the field of catalyst preparation. Summary of the invention
[0007] Terms and Claims of the Present Invention:
[0008] 1. As used herein, the articles "a", "an" and "the" include plural referents unless expressly limited to one or more referents otherwise.
[0009] 2. As used herein, numerical range: Unless otherwise expressly indicated, all ranges or ratios disclosed herein will be understood to include any and all sub-ranges or sub-ratios contained therein. For example, a range or ratio of 1 to 30 stated should be considered to be included between a minimum value of 1 and a maximum value of 30, and any sub-range or sub-ratio, integer, decimal, or sub-range or sub-ratio consisting of integers or decimals including the end points.
[0010] 3. As used herein, "higher alcohol" refers specifically to a straight-chain alcohol having 2 to 6 carbon atoms, i.e., C 2-6 OH.
[0011] The invention discloses a catalyst for synthesizing higher alcohols by hydrogenating CO2, and a preparation method and application thereof. A plurality of additives are introduced into the catalyst for modification, and a mechanical ball milling method is used to improve the dispersion of active components, so as to prepare a catalyst with high CO2 conversion rate and good higher alcohol selectivity.
[0012] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0013] In a first aspect, the present invention provides a catalyst for synthesizing higher alcohols by hydrogenation of CO2, the catalyst comprising an active component, an additive I, and an additive II;
[0014] The active components are Fe and Zn, and the molar ratio of Fe to Zn is 2-10:1;
[0015] Preferably, the molar ratio of Fe to Zn is: 3-10:1;
[0016] Preferably, the molar ratio of Fe to Zn is: 3-5:1;
[0017] Preferably, the molar ratio of Fe to Zn is 3:1.
[0018] The auxiliary agent I is one or more of Na, K, Rb, and Cs, with a mass fraction of 0.2-3%;
[0019] Preferably, the auxiliary agent I is K;
[0020] Preferably, the mass fraction of the auxiliary agent I is 0.5-2%;
[0021] The auxiliary agent II is one or more of Zr and Mn, with a mass fraction of 3-10%.
[0022] Preferably, the auxiliary agent II is Zr;
[0023] Preferably, the mass fraction of the auxiliary agent II is 6-10%.
[0024] In a second aspect, the present invention provides a method for preparing a catalyst for preparing higher alcohols by hydrogenation of CO2, comprising the following steps:
[0025] (1) putting Fe salt, Zn salt, the precursor of additive I and the precursor of additive II into a ball mill for grinding;
[0026] (2) The ground sample is dried and calcined to obtain a catalyst.
[0027] Preferably, the precursors of the Fe salt, Zn salt and additive II in step (1) can be selected from one or more of their corresponding nitrates, chlorides, sulfates and acetates;
[0028] Preferably, the precursor of the auxiliary agent I can be selected from one or more of its corresponding carbonates and hydroxides.
[0029] Preferably, the ball milling speed in step (1) is 200-500 r / min; and the ball milling time is 0.5-4 h.
[0030] Preferably, in step (2), the drying temperature is 120° C., and the drying time is 12-24 h; the roasting temperature is 350-450° C., and the roasting time is 2-5 h.
[0031] In a third aspect, the present invention also provides an application of a catalyst for synthesizing higher alcohols by hydrogenation of CO2, comprising the following steps:
[0032] (1) Mixing the catalyst with quartz sand and loading it into a fixed bed constant temperature zone;
[0033] (2) After the catalyst is reduced, it is cooled to the reaction temperature, the raw gas is introduced, and the reaction is carried out under back pressure.
[0034] Preferably, the process parameters are as follows:
[0035] The mesh numbers of the catalyst and quartz sand are both 40-60 mesh, and the mass ratio of the catalyst to the quartz sand is 1:2;
[0036] The reducing gas is selected from any one of pure H2, pure CO, a mixture of H2 and Ar with a volume fraction of 10%, and a mixture of CO and Ar with a volume fraction of 10%;
[0037] The reduction temperature is 350-400°C and the reduction time is 2-8h;
[0038] The volume ratio of raw gas is H2:CO2:N2=18:6:1, and the space velocity is 3000-6000mLg cat -1 h -1 .
[0039] The reaction temperature is 240-320°C, and the reaction pressure is 3-5MPa.
[0040] In a fourth aspect, the present invention also provides a method for preparing higher alcohols using a CO2 hydrogenation catalyst, comprising the following steps:
[0041] (1) Mixing CO2 hydrogenation catalyst with quartz sand and loading it into a fixed bed constant temperature zone;
[0042] (2) After the CO2 hydrogenation catalyst is reduced, it is cooled to the reaction temperature, the raw gas is introduced, and the reaction is carried out under back pressure.
[0043] Preferably, the process parameters are as follows:
[0044] The mesh numbers of the catalyst and quartz sand are both 40-60 mesh, and the mass ratio of the catalyst to the quartz sand is 1:2;
[0045] The reducing gas is selected from any one of pure H2, pure CO, a H2 / Ar mixed gas with a volume fraction of 10%, and a CO / Ar mixed gas with a volume fraction of 10%;
[0046] The reduction temperature is 350-400°C and the reduction time is 2-8h;
[0047] The volume ratio of raw gas is H2:CO2:N2=18:6:1, and the space velocity is 3000-6000mLg cat -1 h -1 .
[0048] The reaction temperature is 240-320°C, and the reaction pressure is 3-5MPa.
[0049] The beneficial effects of the present invention are:
[0050] (1) Precise control: The catalyst preparation method can precisely control the distribution of active components;
[0051] (2) Excellent performance: The catalyst exhibits excellent catalytic activity and selectivity in the CO2 hydrogenation reaction to synthesize higher alcohols;
[0052] (3) Environmentally friendly: The preparation process of the catalyst avoids the use of solvents, reducing environmental impact;
[0053] (4) Easy to operate: The preparation process of the catalyst simplifies the catalyst preparation process and is easy to operate and manage;
[0054] (5) Scalability: The catalyst is suitable for transformation from small-scale laboratory to large-scale industrial production and has good scale-up potential;
[0055] (6) Large-scale production: Due to the ease of operation and scalability of the catalyst, this technology is easy to achieve large-scale production to meet industrial needs. DETAILED DESCRIPTION
[0056] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0057] The technical details of the present invention are described in detail by the following examples. It should be noted that the examples are only used to further illustrate the technical features of the present invention, rather than to limit the protection scope of the present invention.
[0058] Unless otherwise specified, all commodities or reagents in the present invention were purchased through market channels.
[0059] Preparation method of catalyst for synthesizing higher alcohols by CO2 hydrogenation
[0060] Weigh Fe salt, Zn salt, precursor of additive I and precursor of additive II and put them into a polytetrafluoroethylene ball mill for grinding, the ball mill speed is 200-500r / min; the ball milling time is 0.5-4h. The ball-milled sample is placed in a 110℃-130℃ oven for drying for 12-24h, calcined in a muffle furnace at 350-450℃ for 2-5h, and the calcined sample is pressed and sieved into uniform particles of 40-60 mesh to obtain a catalyst.
[0061] Performance Evaluation of Catalysts for Synthesis of Higher Alcohols by CO2 Hydrogenation
[0062] Weigh 1g of catalyst and 2g of quartz sand, mix them and load them into the fixed bed constant temperature zone. The catalyst is first reduced at 350℃ for 3h in H2 atmosphere, and then after cooling to 280℃, H2, CO2, and N2 raw gas with a volume ratio of 18:6:1 is introduced at a space velocity of 3000mLg cat -1 h -1 , the reaction pressure is 3MPa.
[0063] 1. Investigation of Fe / Zn molar ratio
[0064] Example 1 Catalyst for hydrogenation synthesis of higher alcohols
[0065] Composition ratio: Fe:Zn molar ratio = 2:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0066] According to the molar ratio of Fe to Zn = 1:1, 33.6g of Fe(NO3)3·9H2O and 12.4g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and 0.4g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst. 3, According to the Zr content accounting for 6% of the total mass of the catalyst, 3.16g of Zr(NO3)4·5H2O was weighed. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven for drying for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0067] Example 2 Catalyst for hydrogenation synthesis of higher alcohols
[0068] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0069] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and 0.4g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst. 3, According to the Zr content accounting for 6% of the total mass of the catalyst, 3.16g of Zr(NO3)4·5H2O was weighed. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven for drying for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0070] Example 3 Catalyst for hydrogenation synthesis of higher alcohols
[0071] Composition ratio: Fe:Zn molar ratio = 5:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0072] According to the molar ratio of Fe and Zn = 5:1, 42.1g of Fe(NO3)3·9H2O and 6.2g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, 0.4g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst, and 3.16g of Zr(NO3)4·5H2O was weighed according to the Zr content accounting for 6% of the total mass of the catalyst. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, the speed of the ball mill was 400r / min, the time was 2h, and then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0073] Example 4 Catalyst for hydrogenation synthesis of higher alcohols
[0074] Composition ratio: Fe:Zn molar ratio = 10:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0075] According to the molar ratio of Fe to Zn = 10:1, 45.9 g of Fe(NO3)3·9H2O and 3.4 g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and 0.4 g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst. 3,According to the Zr content accounting for 6% of the total mass of the catalyst, 3.16g of Zr(NO3)4·5H2O was weighed. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven for drying for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0076] Comparative Example 1
[0077] According to the comparative literature "Effect of Mn as a promoter in CuFe-based catalysts for hydrogenation of CO2 to produce low-carbon alcohols" published by Zhang Xinxin et al. in the Journal of Chemistry of Universities, a comparative experiment was set up. Specifically, the molar ratio of Mn, Cu, Fe and Zn was 0.1:1:1:1, the mass fraction of K was 3%, 1.0 g of Mn(NO3)2·4H2O, 9.6 g of Cu(NO3)2·3H2O, 16.3 g of Fe(NO3)3·9H2O and 12.0 g of Zn(NO3)2·6H2O were dissolved in 100 mL of deionized water, and 2 mol / L K2CO3 solution, and continued stirring for 5h; then fully washed with 1L deionized water to thoroughly wash away potassium ions, the precipitate was placed in a 60℃ forced air oven to dry for 12h, placed in a muffle furnace and heated to 400℃ at a heating rate of 5℃ / min and calcined for 3h to obtain MnCuFeZn quaternary oxide. 2.1g of K2CO3 was weighed and dissolved in a certain volume of deionized water, and then dropped onto the MnCuFeZn quaternary oxide solid, magnetically stirred at room temperature for 5h, placed in a 60℃ forced air oven to dry for 12h, and then heated to 400℃ at a heating rate of 5℃ / min in a muffle furnace and calcined for 3h to obtain a catalyst.
[0078] Comparative Example 2
[0079] Comparative Example 2 was set up according to the catalyst preparation method disclosed in Chinese patent CN116099540A, specifically: according to the mass ratio of indium oxide precursor: alkali metal auxiliary agent precursor: metal auxiliary agent precursor of 53-96: 1-10: 2-14, 5.5g In2(SO4)3 was weighed and dissolved in 20mL deionized water, 0.2M sodium hydroxide methanol solution was added dropwise to the In2(SO4)3 solution under 20°C water bath conditions, and stirred continuously until pH = 8.5, aged for 48 hours under 20°C water bath conditions, filtered, and washed to obtain To In2O3 precursor, put the In2O3 precursor into a 60°C oven and dry it for 12 hours, and put the dried indium oxide precursor into a 400°C muffle furnace and calcine it for 1 hour to obtain In2O3; weigh 0.3g of NaNO3, 0.3g of Fe(NO3)3, and 0.2g of NiNO3 and dissolve them in 10mL of deionized water to obtain an auxiliary solution; add indium oxide to the auxiliary solution and stir continuously, put the obtained slurry into a 150°C oven and dry it for 2 hours, and put the dried mixture into a 300°C muffle furnace and calcine it for 6 hours to obtain a catalyst.
[0080] Comparative Example 3
[0081] Composition ratio: Fe:Zn molar ratio = 1:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0082] According to the molar ratio of Fe to Zn = 1:1, 25.1g of Fe(NO3)3·9H2O and 18.5g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and 0.4g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst. 3, According to the Zr content accounting for 6% of the total mass of the catalyst, 3.16g of Zr(NO3)4·5H2O was weighed. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven for drying for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0083] Comparative Example 4
[0084] Composition ratio: Fe:Zn molar ratio = 12:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0085] According to the molar ratio of Fe to Zn = 12:1, 46.7g of Fe(NO3)3·9H2O and 2.9g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and 0.4g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst. 3, According to the Zr content accounting for 6% of the total mass of the catalyst, 3.16g of Zr(NO3)4·5H2O was weighed. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven for drying for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0086] The catalytic performance of Examples 1-4 and Comparative Examples 1-4 was tested according to the above catalyst performance evaluation method. The specific test results are shown in Table 1.
[0087] Table 1 Catalytic performance results of Examples 1-4 and Comparative Examples 1-4
[0088]
[0089] From the data in Table 1, it can be seen that compared with the prior art, when the molar ratio of Fe to Zn is 2-10:1, the catalytic performance of CO2 hydrogenation to higher alcohols can be improved. Compared with Comparative Examples 3 and 4, when the molar ratio of Fe to Zn is 2-10:1, the catalytic performance of CO2 hydrogenation to higher alcohols can be improved.
[0090] When the molar ratio of Fe and Zn is 2-10:1, the catalytic performance of CO2 hydrogenation to higher alcohols can be improved; when the molar ratio of Fe and Zn is 3-10:1, the catalytic performance of CO2 hydrogenation to higher alcohols is better; when the molar ratio of Fe and Zn is 3-5:1, the catalytic performance of CO2 hydrogenation to higher alcohols is better; when the molar ratio of Fe and Zn is 3:1, the best CO2 conversion rate and higher alcohol selectivity can be obtained, which are 45.4% and 52.6% respectively.
[0091] 2. Investigation of Types of Additives I
[0092] Example 5 Catalyst for hydrogenation synthesis of higher alcohols
[0093] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0094] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, Na2CO3 was selected as the precursor of the additive I, 0.52g of Na2CO3 was weighed according to the Na content accounting for 2% of the total mass of the catalyst, and 3.2g of Zr(NO3)4·5H2O was weighed according to the Zr content accounting for 6% of the total mass of the catalyst. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, the ball milling speed was 400r / min, the time was 2h, and then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0095] Example 6 Catalyst for hydrogenation synthesis of higher alcohols
[0096] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0097] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, Rb2CO3 was selected as the precursor of additive I, 0.51g of Rb2CO3 was weighed according to the Rb content accounting for 2% of the total mass of the catalyst, and 3.2g of Zr(NO3)4·5H2O was weighed according to the Zr content accounting for 6% of the total mass of the catalyst. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, the ball milling speed was 400r / min, the time was 2h, and then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0098] Example 7 Catalyst for hydrogenation synthesis of higher alcohols
[0099] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0100] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, Cs2CO3 was selected as the precursor of additive I, 0.46g of Cs2CO3 was weighed according to the Cs content accounting for 2% of the total mass of the catalyst, and 3.2g of Zr(NO3)4·5H2O was weighed according to the Zr content accounting for 6% of the total mass of the catalyst. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, the ball milling speed was 400r / min, the time was 2h, and then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0101] The catalytic performance of Examples 5-7 was tested according to the above catalyst performance evaluation method. The specific test results are shown in Table 2.
[0102] Table 2 Catalytic performance results of Examples 2, 5, 6, 7 and Comparative Examples 1 and 2
[0103]
[0104] It can be seen from the data in Table 2 that compared with the prior art, the addition of Na, K, Rb, and Cs as auxiliary agent I can greatly improve the selectivity of higher alcohols and the CO2 conversion rate is also improved. Preferably, when auxiliary agent I is K, the selectivity of higher alcohols is most significantly improved, which is 52.6%, and the CO2 conversion rate is the highest, which is 45.4%.
[0105] 3. Investigation of the types of additives II
[0106] Example 8 Catalyst for hydrogenation synthesis of higher alcohols
[0107] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0108] According to the molar ratio of Fe and Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of auxiliary agent I, and 0.39g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst. Mn(NO3)2·4H2O was selected as the precursor of auxiliary agent II, and the Mn content accounted for 6% of the total mass of the catalyst, with a mass of 2.99g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined at 400℃ in a muffle furnace for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0109] Comparative Example 5
[0110] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 0% of the total mass of the catalyst.
[0111] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and 0.36g of K2CO3 was weighed according to the K content accounting for 2% of the total mass of the catalyst. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, the speed of the ball mill was 400r / min, the time was 2h, and then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0112] Comparative Example 6
[0113] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 0% of the total mass of the catalyst.
[0114] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, and Na2CO3 was selected as the precursor of the additive I. According to the Na content accounting for 2% of the total mass of the catalyst, 0.47g of Na2CO3 was weighed. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0115] Comparative Example 7
[0116] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 0% of the total mass of the catalyst.
[0117] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, Rb2CO3 was selected as the precursor of additive I, and 0.46g of Rb2CO3 was weighed according to the Rb content accounting for 2% of the total mass of the catalyst. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, the speed of the ball mill was 400r / min, the time was 2h, and then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0118] Comparative Example 8
[0119] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 0% of the total mass of the catalyst.
[0120] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, Cs2CO3 was selected as the precursor of additive I, and 0.42g of Cs2CO3 was weighed according to the Cs content accounting for 2% of the total mass of the catalyst. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, the speed of the ball mill was 400r / min, the time was 2h, and then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0121] Comparative Example 9
[0122] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0123] According to the molar ratio of Fe and Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of auxiliary agent I, and the K content accounted for 2% of the total mass of the catalyst. 0.42g of K2CO3 was weighed, and Al(NO3)3·9H2O was selected as the precursor of auxiliary agent II, and the Al content accounted for 6% of the total mass of the catalyst, with a mass of 9.8g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0124] The catalytic performance of Example 8 and Comparative Examples 5-9 was tested according to the above-mentioned catalyst performance evaluation method. The specific test results are shown in Table 3.
[0125] Table 3 Catalytic performance results of Example 8 and Comparative Examples 5-9
[0126]
[0127] Comparison between Examples 2, 5, 6, and 7 and Comparative Examples 5-8 shows that the CO2 conversion rate and higher alcohol selectivity are greatly improved after the introduction of additive II into the catalyst with K, Na, Rb, and Cs as additive I. Comparison between Examples 2 and 8 and Comparative Example 9 shows that the addition of Mn and Zr as additive II greatly improves the CO2 conversion rate and higher alcohol selectivity, and preferably the catalyst performance is best when additive II is Zr.
[0128] 4. Investigation on the content of additive I
[0129] Example 9 Catalyst for hydrogenation synthesis of higher alcohols
[0130] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 0.5% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0131] According to the molar ratio of Fe and Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of auxiliary agent I, and 0.1g of K2CO3 was weighed according to the K content accounting for 0.5% of the total mass of the catalyst. Zr(NO3)4·5H2O was selected as the precursor of auxiliary agent II, and the Zr content accounted for 6% of the total mass of the catalyst, with a mass of 3.09g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0132] Example 10 Catalyst for hydrogenation synthesis of higher alcohols
[0133] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 1% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0134] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and 0.19g of K2CO3 was weighed according to the K content accounting for 1% of the total mass of the catalyst. Zr(NO3)4·5H2O was selected as the precursor of additive II, and the Zr content accounted for 6% of the total mass of the catalyst, with a mass of 3.11g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets.
[0135] Embodiment 11 Catalyst for hydrogenation synthesis of higher alcohols
[0136] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 3% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0137] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of auxiliary agent I, and 0.6g of K2CO3 was weighed according to the K content accounting for 3% of the total mass of the catalyst. Zr(NO3)4·5H2O was selected as the precursor of auxiliary agent II, and the Zr content accounted for 6% of the total mass of the catalyst, with a mass of 3.2g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets.
[0138] Comparative Example 10
[0139] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 5% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0140] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of auxiliary agent I, and 1.03g of K2CO3 was weighed according to the K content accounting for 5% of the total mass of the catalyst. Zr(NO3)4·5H2O was selected as the precursor of auxiliary agent II, and the Zr content accounted for 6% of the total mass of the catalyst, with a mass of 3.29g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets.
[0141] Comparative Example 11
[0142] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 0% of the total mass of the catalyst, and the content of additive II accounts for 6% of the total mass of the catalyst.
[0143] According to the molar ratio of Fe to Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, and Zr(NO3)4·5H2O was selected as the precursor of additive II. The Zr content accounted for 6% of the total mass of the catalyst, and the mass was 3.07g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0144] The catalytic performance of Examples 9, 10, 11 and Comparative Examples 10, 11 was tested according to the above catalyst performance evaluation method. The specific test results are shown in Table 4.
[0145] Table 4 Catalytic performance results of Examples 2, 9, 10, 11 and Comparative Examples 10 and 11
[0146]
[0147]
[0148] From the data in Table 4, it can be seen that the addition of 0.2-3% by mass of the additive I significantly improves the selectivity of CO2 hydrogenation to synthesize higher alcohols and the CO2 conversion rate. Preferably, when the mass fraction of the additive I is 0.5-2%, the catalyst performance is improved more significantly.
[0149] 5. Investigation on the content of additive II
[0150] Example 12 Catalyst for hydrogenation synthesis of higher alcohols
[0151] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 3% of the total mass of the catalyst.
[0152] According to the molar ratio of Fe and Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of auxiliary agent I, and the K content accounted for 2% of the total mass of the catalyst. 0.38g of K2CO3 was weighed, and Zr(NO3)4·5H2O was selected as the precursor of auxiliary agent II, and the Zr content accounted for 3% of the total mass of the catalyst, with a mass of 1.51g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0153] Embodiment 13 Catalyst for hydrogenation synthesis of higher alcohols
[0154] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 10% of the total mass of the catalyst.
[0155] According to the molar ratio of Fe and Zn = 3:1, 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O were weighed, K2CO3 was selected as the precursor of additive I, and the K content accounted for 2% of the total mass of the catalyst. 0.42g of K2CO3 was weighed, and Zr(NO3)4·5H2O was selected as the precursor of additive II, and the Zr content accounted for 10% of the total mass of the catalyst, with a mass of 5.6g. The above materials were placed in a 200mL polytetrafluoroethylene ball mill, and the ball milling speed was 400r / min for 2h. Then the ball-milled sample was placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst was pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0156] Comparative Example 12
[0157] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 1% of the total mass of the catalyst.
[0158] Preparation method: According to the molar ratio of Fe and Zn = 3:1, weigh 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O, select K2CO3 as the precursor of additive I, and the K content accounts for 2% of the total mass of the catalyst. Weigh 0.37g of K2CO3, and select Zr(NO3)4·5H2O as the precursor of additive II, and the Zr content accounts for 1% of the total mass of the catalyst, with a mass of 0.49g. The above materials are placed in a 200mL polytetrafluoroethylene ball mill, the ball milling speed is 400r / min, the time is 2h, and then the ball-milled sample is placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst is pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0159] Comparative Example 13
[0160] Composition ratio: Fe:Zn molar ratio = 3:1, the content of additive I accounts for 2% of the total mass of the catalyst, and the content of additive II accounts for 12% of the total mass of the catalyst.
[0161] Preparation method: According to the molar ratio of Fe and Zn = 3:1, weigh 37.8g of Fe(NO3)3·9H2O and 9.3g of Zn(NO3)2·6H2O, select K2CO3 as the precursor of additive I, and the K content accounts for 2% of the total mass of the catalyst. Weigh 0.43g of K2CO3, and select Zr(NO3)4·5H2O as the precursor of additive II, and the Zr content accounts for 12% of the total mass of the catalyst, with a mass of 6.94g. The above materials are placed in a 200mL polytetrafluoroethylene ball mill, the ball milling speed is 400r / min, the time is 2h, and then the ball-milled sample is placed in a 120℃ oven to dry for 12h, and then calcined in a muffle furnace at 400℃ for 3h to obtain a fresh catalyst. The fresh catalyst is pressed into tablets and sieved into uniform particles of 40-60 mesh.
[0162] The catalytic performance of Examples 14 and 15 and Comparative Examples 8 and 9 was tested according to the above-mentioned catalyst performance evaluation method. The specific test results are shown in Table 5.
[0163] Table 5 Catalytic performance results of Examples 2, 12, 13 and Comparative Examples 12, 13
[0164]
[0165] From the data in Table 5, it can be seen that the content of additive II has an effect on the catalytic performance of CO2 hydrogenation to higher alcohols. When the mass fraction of additive II is 3-10%, the CO2 conversion rate is improved. Preferably, when the mass fraction of additive II is 6-10%, the catalyst performance is improved to the greatest extent.
[0166] The catalytic performance of the catalyst is not the better the more additives are added. As shown in Tables 4 and 5, excessive additives will block the pores of the catalyst, cover the active sites, and lead to reduced catalytic performance. However, the present application can further improve the performance of the catalyst by introducing new additives when the addition amount of a single additive reaches the maximum. Preferably, when additive I is K and accounts for 0.5-2% of the total mass of the catalyst, and additive II is Zr and accounts for 6-10% of the total mass of the catalyst, the CO2 conversion rate and higher alcohol selectivity can be further improved to 45.4% and 52.6%, respectively.
[0167] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can further make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any equivalent changes, modifications and evolutions made by technicians familiar with this profession without departing from the spirit and scope of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention and are within the protection scope of the present invention.
[0168] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A catalyst for synthesizing higher alcohols by hydrogenation of CO2, characterized in that: The catalyst comprises an active component, an auxiliary agent I and an auxiliary agent II; The active components are Fe and Zn, and the molar ratio of Fe to Zn is 2-10:1; The additive I is one or more of Na, K, Rb, and Cs, and the additive I accounts for 0.2-3% of the total mass of the catalyst; The auxiliary agent II is one or more of Zr and Mn, and the auxiliary agent II accounts for 3-10% of the total mass of the catalyst.
2. The catalyst according to claim 1, characterized in that The mass fraction of the said additive I is 0.5-2% of the total mass of the catalyst, and the mass fraction of the said additive II is 6-10% of the total mass of the catalyst; and / or The auxiliary agent I is K; and / or The auxiliary agent II is Zr.
3. A method for preparing a catalyst as claimed in any one of claims 1 to 2, characterized in that: The steps include: (1) grinding Fe salt, Zn salt, precursor of additive I and precursor of additive II; (2) The ground sample is dried and calcined to obtain a catalyst.
4. The preparation method according to claim 3, characterized in that: The precursors of the Fe salt, Zn salt and additive II in step (1) can be independently selected from one or more of their corresponding nitrates, chlorides, sulfates and acetates; The precursor of the auxiliary agent I can be selected from one or more of its corresponding carbonates and hydroxides.
5. The preparation method according to claim 3, characterized in that: The grinding in step (1) is ball milling, the rotation speed of the ball mill is 200-500r / min, and the time is 0.5-4h.
6. The preparation method according to claim 3, characterized in that: The drying temperature in step (2) is 110°C-130°C and the drying time is 12-24h; The calcination temperature is 350-450° C. and the calcination time is 2-5 hours.
7. Use of the catalyst as claimed in any one of claims 1 to 6 in the synthesis of higher alcohols by CO2 hydrogenation.
8. A method for preparing higher alcohols, characterized in that: It is prepared by hydrogenating CO2 as a raw material using the catalyst described in any one of claims 1 to 6.
9. The method according to claim 8, characterized in that The steps include: S1, mixing the catalyst with quartz sand for reduction; S2, cooling to reaction temperature, introducing raw gas, and reacting; The mesh size of the catalyst and quartz sand in S1 is 40-60 mesh; The mass ratio of the catalyst to the quartz sand in S1 is 1:2; The reduction temperature in S1 is 350°C-400°C and the time is 2-8h; The raw gas in S2 is a mixed gas of H2, CO2 and N2; The reaction temperature in S2 is 240-320° C., and the reaction pressure is 3-5 MPa.
